Penner's serotype 4 of Campylobacter jejuni has a lipopolysaccharide that bears a GM1 ganglioside epitope as well as one that bears a GD1 a epitope. - Yuki, N (1994)
The carbohydrate structures of lipopolysaccharides (LPSs) of Campylobacter jejuni strains belonging to Penner's serotypes (PEN) 1, 2, 4, 19, 23, and 36 were studied by thin-layer chromatography and immunostaining with several monoclonal antiganglioside antibodies. Anti-GM1 and anti-GD1a antibodies reacted with the LPSs of PEN 1, 4, and 19. Aspinall et al. (G. O. Aspinall, A. G. McDonald, T. S. Raju, H. Pang, A. P. Moran, and J. L. Penner. Eur. J. Biochem. 213:1017-1027, 1993) recently reported that the LPS of PEN 4 has a GD1a ganglioside-like structure rather than a GM1-like structure. We found that the LPS fraction of C. jejuni (PEN 4) has an LPS that bears a GM1 epitope as well as an LPS that bears a GD1a epitope.